CP-228 Evolution of the consumption of anxiolytics and hypnotics in a health area. (25th February 2017) - Abel, T; Miguel, B Juan; Ana, A; Carmen, C; Carmen, V; Carles, I
Abstract : Background: Benzodiazepines are a group of medicines whose consumption is increasing in Spain. Purpose: To study sedative and hypnotic drug consumption, expressed as defined daily doses by 1000 inhabitants (DHD), and to compare consumption as definite daily doses (DDD) with the variation in the population in a health area. Material and methods: This was a descriptive retrospective study of dispensations of medical specialties belonging to the ATC classification system N05B (antianxiety) and N05C (hypnotics and sedatives), carried out in a health area between 2010 and 2015. The variables considered were: year, DDD, DHD, active principle and number of inhabitants. Results: Global consumption of anxiolytics and hypnotics has grown from 84.7 DHD in 2010 to 92.9 DHD in 2015, representing an increase of 9.8%. The anxiolytics group experienced an increase of 7.5% in this period of time, the most widely consumed drugs being lorazepam and alprazolam with an average of 29.4±1.5 and 12.8±0.2 DHD, respectively. The largest increase was for diazepam (31.4%) while the largest decrease was for bentazepam (63.8%). On the other hand, the hypnotics group had an increase of 14.6%, the most widely consumed being lormetazepam and zolpidem, with an average of 16.1±1.9 and 1.6±0.6 DHD, respectively. The drug with the greatest increase was lormetazepam (19.5%) while loprazolam had the greatest decrease (57.7%). Moreover, the absolute data of consumption expressed as totals were 5 464 872, 5 407 847, 5 331 180, 5 419 403, 5 556 624, 5 557 246 for the years of the period studied. In terms of population data in the study years 2010, 2011, 2012, 2013, 2014 and 2105, there were, respectively, 176 874, 170 268, 162 559, 162 010, 162 352 and 163 792 inhabitants. Conclusion: In accordance with similar studies carried out in Spain, there was a clear trend towards an increase in consumption of sedatives and hypnotics per inhabitant in our health area. This increase occurred mainly in the group of hypnotic with an increase that was almost doubled that for anxiolytics. The tendency to a population decline in the first half of the period of our study and a stable population in the second half, had no parallel in the continued upward trend in total consumption of anxiolytics and sedatives. No conflict of interest